Bidirectional crosstalk between neutrophils and adipocytes promotes adipose tissue inflammation. Issue 11 (29th July 2019) - Watanabe, Yasuharu; Nagai, Yoshinori; Honda, Hiroe; Okamoto, Naoki; Yanagibashi, Tsutomu; Ogasawara, Masaru; Yamamoto, Seiji; Imamura, Ryu; Takasaki, Ichiro; Hara, Hiromitsu; Sasahara, Masakiyo; Arita, Makoto; et al.
Abstract : Chronic activation of the IL‐1β system in adipose tissue on metabolic disorders is well demonstrated. However, a mechanism for its expression and activation in the tissue has remained unexplored. Here, we demonstrate that IL‐1β transcript was enriched in neutrophils of white adipose tissue (WAT) from lean mice. Mechanistically, the interaction of neutrophils with adipocytes induced IL‐1β expression via NF‐κB pathway. Lipolysis of adipocytes accumulated neutrophils prior to macrophages in WAT and produced high levels of IL‐1β via an inflammasome pathway. Leukotriene B4 (LTB4 ) production in WAT also contributed to neutrophil accumulation. Furthermore, an LTB4 ‐inflammasome axis contributed to the expression of chemotactic molecules involved in high‐fat diet‐induced macrophage infiltration into WAT. We have identified previously unappreciated roles for neutrophils in the development of adipose tissue inflammation: robust IL‐1β production and infiltration of macrophages to initiate chronic inflammation.—Watanabe, Y., Nagai, Y., Honda, H., Okamoto, N., Yanagibashi, T., Ogasawara, M., Yamamoto, S., Imamura, R., Takasaki, I., Hara, H., Sasahara, M., Arita, M., Hida, S., Taniguchi, S., Suda, T., Takatsu, K. Bidirectional crosstalk between neutrophils and adipocytes promotes adipose tissue inflammation. FASEB J. 33, 11821‐11835 (2019). www.fasebj.org